KEPERCAYAAN PEDAGANG TERHADAP WONG PINTER DALAM MENUNJANG USAHA DAGANG DI PASAR BINTORO DEMAK - Indrasuari, Apita Fikri (Solidarity: Journal of Education, Society and Culture, 2012)
In the district there are some people, especially Demak traders who believe wong clever. In running its trading business traders often ask for the blessing of the wong clever, because confidence in the wong clever deemed incompatible with Islamic teachings. The reason the merchant asking for help on wong berdagangnya clever in luck, because in practice the ritual wong clever use of the rite that is considered not to deviate from Islamic teachings. Traders confidence to wong clever as it is influenced by cultural heritage. Wong clever contained in Demak is considered the spiritual leader of Islam that can help one to solve problems in ways that they do not deviate from the religion of Islam. The merchants, especially merchants in the Market Bintoro Demak that most traders are Javanese who still believe in things unseen, which is mixed with local customs. Lots of views on the wong clever, one of which is a clever wong is thought to help people in every way. The other view says that wong clever use of objects occultism avoided Demak City community, because most people have of Islam is very strong. There is a myth that success is within reach for Muslim traders, often asking for help and consult on a more clever wong can be helpful because the rituals of the rite of Islam as compared to using things that are unseen